O surto de Zika vírus: produção científica após Declaração de Emergência Nacional em Saúde Pública - Freitas, Paula de Souza Silva (2018)
Background: In 2015, there was a dramatic increase in Zika virus infection in the Americas, Brazil being the country most affected, with an average estimate of 1.5 million cases of virus infection. This led the Ministry of Health to declare a national emergency situation . Objective: To identify what was produced in the scientific field on the infection of the Zika virus after the declaration of public health emergency of national importance. Method: This is an integrative review of the literature, with articles published after the declaration of national emergency in public health, in the electronic databases available at the Regional Library of Medicine. The descriptors used were Zika virus and Infection by Zika, resulting in 428 publications, but with application of the inclusion criteria were reduced to 40 studies. Of this total, 7 articles were chosen to be used in the integrative review. Results: All articles were published in the English language, in journals related to public health and with a high impact factor. As for the year of publication, all were published in 2016. Regarding the nationality of the articles, it was found that three studies were conducted in French Polynesia, two in Brazil, one in Colombia and one in Slovenia. Regarding the type of research design, three studies were clinical studies, two retrospective, one case-control and one experimental. Conclusion: It is observed that the production by scientific articles after the sanitary emergency declaration, resulted in the stable development of the scientific interest in the Zika virus and in considerable growth in the number of publications with the theme